Toponyms of Pontevedra province. An outline of problems - Pawlikowska, Marta Anna (Geographical names in physical space, 2016)
Toponymy, both macro and micro, function in a linguistic reality that influence and change it. In the north – west region of Spain, Galicia, after years of strong, centralized, supporting only Spanish language policy led by General Francisco Franco, was the era of democratization and resulted in the return to original names in the Galician language. This process has been slow, because even though regulations are clear and officially changed toponyms administrative function in reality the words do not always coincide with the real use of them by the Galician people. Until now, in the minds of many people, Spanish toponyms function and not their official version in Galician. Language policy carried out in Galicia affects not only the education and the media, but also something that affects our daily life, though rarely we pay attention to it, i.e. the toponyms.